Fiction and Poetry in Contemporary Peru - Martos Carrera, Marco (2013)
Panorama descriptivo y analítico de las principales tendencias de la literatura peruana, de la segunda mitad del siglo XX. Se hace particular hincapié en las manifestaciones de su narrativa y del discurso poético. The article describes and analyzes the main tendencies of Peruvian literature in the second half of the twentieth-century, with particular emphasis on narrative and poetic discourse.